2008
DOI: 10.1016/j.anifeedsci.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Phytate utilization and phosphorus excretion by broiler chickens fed diets containing cereal grains varying in phytate and phytase content

Abstract: Eighty, 12-day-old, male broiler chicks, were fed one of four diets to determine the effects of feeding grains varying in phytate phosphorus (P) and intrinsic phytase activity on ileal and excreta P digestibility and composition. The diets contained approximately 970.7 g grain kg −1 (maize, high fat-low lignin oat, normal barley or low-phytate barley) with the cereal supplying the sole source of dietary P. The diets were fed for a 7-day acclimation period followed by a 2 day excreta collection while ileal dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 14 publications
5
18
1
Order By: Relevance
“…The authors concluded that the absorbed P was re-directed into the excreta, likewise via the urine. A similar finding has been reported in broiler chickens by Leytem et al (2008b).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The authors concluded that the absorbed P was re-directed into the excreta, likewise via the urine. A similar finding has been reported in broiler chickens by Leytem et al (2008b).…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown in the excreta of laying hens on a maize-soyabean diet (Marounek et al, 2008a), broiler chickens (Leytem et al, 2008b), and in other animal species (for references see Marounek et al, 2008b). As for the total P concentration in the excreta, similar values were reported in laying hens on a wheat-maize-soyabean diet by Zobac et al (1998).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Destruction of endogenous phytase had only a little negative influence (P > 0.05) on the total P retention coefficient and bone mineral density. Similar results with different intrinstic phytase activity of cereal grains (16-99 U/kg) were reported by Leytem et al (2008). In contrast, the effect of endogenous phytase was significant (P < 0.05) in the present study.…”
Section: Resultssupporting
confidence: 39%
“…The low availability of native phosphorus from the phytates present in natural feeds, especially in grains (the main components of poultry diets), makes it necessary to add microbial phytases to diets (Leytem et al, 2008). Nonetheless, the supplementation of phosphates, inorganic phosphorus sources, in broiler diets is still indispensable.…”
Section: Introductionmentioning
confidence: 99%